The influence of maturation on the reliability of the Nordic hamstring exercise in male youth footballers - Fernandes, J. F. T.; Moran, J.; Clarke, H.; Drury, B. (Translational Sports Medicine, 2020)
This study sought to establish the reliability of the Nordic hamstring exercise (NHE) in male youth football players. Sixty-four youth football players completed two x three repetitions of the NHE, separated by 1 week. Eccentric hamstring strength was during the NHE using the NordBord. Participants were categorized via maturity offset (based on peak height velocity [PHV]) and age. For all dependent variables and groups, the typical error (TE) was greater than the smallest worthwhile change. Reliability for left, right, bilateral, and relative peak force for the U11s (TE = 0.26-11.1N, coefficient of variation [CV] = 5.9%-7.4%), U13s (TE = 0.28-17.9N, CVs = 5.6%-7.8%) and U16s (TE = 0.28-24.3, CVs = 6.6%-8.7%) was favorable and demonstrated no clear pattern between groups. According to PHV, those less mature provided smaller TEs (0.22-9.3N) and CVs (4.8%-5.7%) compared with their more mature counterparts (TE = 0.30-22.5N, CVs = 7.2%-8.5%). For all age and maturation groups, imbalances yielded poor reliability (TE = 7.1-10.8N, CVs = 33.1%-38.3%). Eccentric left and right limb, bilateral and relative hamstring peak force can reliably be measured during the NHE across maturation stages. Applied practitioners should exercise caution when assessing muscular imbalances using the NHE.